GaAs / PEDOT: PSS-CNT heterojunction solar cell with electron transport layer and preparation method of GaAs / PEDOT: PSS-CNT heterojunction solar cell
By introducing the ZnO electron transport layer and the PEDOT:PSS@CNT layer in GaAs/PEDOT:PSS heterojunction solar cell, the problem of missing functional layers in the device structure is solved, carrier migration and separation efficiency is improved, and the performance of solar cells is significantly improved.
Patent Information
- Application Number
- CN202411695646.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing GaAs/PEDOT:PSS heterojunction solar cells lack functional layers in the device structure, resulting in non-radiative conformance and carrier loss, limiting their performance improvement.
The ZnO layer was evaporated as an electron transport layer on the back of the GaAs substrate, and PEDOT:PSS and CNT were combined, and PEDOT:PSS@CNT layer was prepared by ultrasonic mixing and spin-coating to promote carrier migration and separation.
By introducing the ZnO electron transport layer and the PEDOT:PSS@CNT layer, the potential barrier of electron transport is effectively reduced, the carrier migration rate and separation efficiency are improved, and the performance of solar cells is significantly improved.
Smart Images

Figure CN119546152A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar cells, and more specifically, to a GaAs / PEDOT:PSS@CNT heterojunction solar cell and a preparation method thereof. Background Art
[0002] In recent years, with the introduction of the concept of carbon neutrality, the development of green and clean energy has become a hot topic of social concern. As the cleanest energy with the largest reserves in nature, solar energy has naturally become the focus of research. As a device that utilizes solar energy, the research on solar cells is of great significance to the development and utilization of solar energy. GaAs is a direct bandgap semiconductor with a bandgap of 1.42eV. Compared with traditional Si, it has the characteristics of higher theoretical efficiency, high carrier mobility, and strong radiation resistance. With these advantages, GaAs solar cells have been widely used in aerospace and other fields. However, the commonly used GaAs solar cell structure is mostly pn homojunction type. Its preparation process requires equipment such as molecular beam epitaxy (MBE) and metal organic chemical vapor deposition (MOCVD) and related epitaxial processes. Most of these equipment are very expensive and the process cost is also relatively high, resulting in the high cost of GaAs solar cells. In contrast, heterojunction solar cells can effectively solve this problem. At present, the development of high-efficiency organic hybrid heterojunction solar cells based on PEDOT:PSS or CNT hole transport films can simplify the device preparation process and significantly reduce its preparation cost, and has been widely studied and reported. In addition to the widely used pn homojunction mentioned above, the structure of solar cells also has a heterojunction type. Its structure is composed of semiconductors and other transparent conductive materials to achieve directional carrier transport. Compared with the pn homojunction, the preparation process of this heterojunction battery eliminates the harsh high-temperature epitaxial step and greatly reduces the cost. Therefore, the development of low-cost, high-performance GaAs heterojunction solar cells has become a research hotspot for many scholars. In addition, with the discovery of conductive polymers in the last century, it has attracted widespread attention and developed rapidly due to its advantages of low cost and simple process. PEDOT:PSS, as a commonly used conductive polymer, is very cheap and has been widely used in the research and development of solar cells, and has achieved certain results. In addition, researchers have previously conducted theoretical calculations and simulations on the theoretical performance limits of GaAs / PEDOT:PSS solar cells, showing great potential. However, in the current GaAs / PEDOT:PSS heterojunction hybrid solar cells, there is still much room for improvement in performance. The reason is that from the perspective of device structure, the absence of many functional layers leads to non-radiative conformity and carrier loss in the device, which results in incomplete device performance. Summary of the invention
[0003] In order to overcome the problems and shortcomings of the above-mentioned prior art, the present invention mainly proposes a method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with a novel electron transport layer, wherein a ZnO layer is evaporated on the back of a GaAs substrate as an electron transport layer, and PEDOT:PSS is combined with CNT, which can effectively promote the carrier migration rate, improve carrier separation, and enhance device performance. Therefore, the GaAs / PEDOT:PSS@CNT heterojunction solar cell with this structure is of great significance to the development of GaAs heterojunction solar cells.
[0004] The purpose of the present invention is achieved through the following technical steps:
[0005] A GaAs / PEDOT:PSS@CNT heterojunction solar cell with a novel electron transport layer, the structure from bottom to top is Au back electrode, ZnO electron transport layer, GaAs substrate, PEDOT:PSS@CNT layer and top electrode, wherein PEDOT:PSS of the PEDOT:PSS@CNT layer refers to an organic polymer, the full name of which is poly (3,4-ethylenedioxythiophene polystyrene sulfonate), and CNT refers to carbon nanotube. The composite layer is made by mixing PEDOT:PSS solution with CNT dispersion by ultrasonic means and then spin coating.
[0006] The open circuit voltage of the solar cell of the present invention is 0.50-0.55V, and the current density is 8.1-10.8mA / cm 2 , the filling factor is 62.1~66.7%, and the photoelectric conversion efficiency is 2.77~3.53%.
[0007] A method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with a novel electron transport layer comprises the following steps:
[0008] (1) Using electron beam evaporation method to evaporate a layer of ZnO on the back of GaAs substrate as an electron transport layer;
[0009] (2) Evaporating a layer of Au on the surface of the ZnO film as the back electrode;
[0010] (3) Preparation of PEDOT:PSS@CNT thin film on GaAs substrate surface;
[0011] (4) Evaporating a layer of one or more composite electrodes selected from Ag, Cr, Ti, Ni, and Au on the surface of PEDOT:PSS@CNT.
[0012] Preferably, the GaAs substrate is n-type doped.
[0013] Preferably, in step (3), the preparation method of the PEDOT:PSS@CNT film is a spin coating method, with a rotation speed of 3000-6000 rpm and a spin coating time of 10s-20s.
[0014] Preferably, in step (1), after the ZnO thin film is evaporated, it needs to be annealed under vacuum conditions at a temperature of 350° C.-400° C.
[0015] Preferably, in step (3), after the preparation of the PEDOT:PSS@CNT film is completed, it needs to be annealed under vacuum conditions at a temperature of 120°C-150°C.
[0016] The specific steps include:
[0017] (1) The GaAs substrate is split into specific sizes according to the requirements to facilitate the subsequent cleaning of the substrate and the preparation of solar cell devices;
[0018] (2) The segmented GaAs substrates were ultrasonically cleaned for 5 minutes using isopropanol, ethanol, and deionized water to remove organic matter on the surface, and then the intrinsic oxide layer on the surface of the GaAs substrate was removed using 10% by mass dilute hydrochloric acid;
[0019] (3) using electron beam evaporation to deposit a layer of ZnO on the back of the GaAs substrate as an electron transport layer;
[0020] (4) Evaporating a layer of metal on the surface of the ZnO film as a back electrode;
[0021] (5) sending the substrate with the evaporated back electrode into an annealing furnace for rapid annealing;
[0022] (6) Preparation of PEDOT:PSS@CNT thin film on GaAs substrate surface;
[0023] (7) A layer of metal is evaporated on the surface of PEDOT:PSS@CNT as the top electrode.
[0024] In the above method step (1), the specific size of the GaAs substrate segmentation can be 0.5cm×0.5cm, 0.7cm×0.7cm, 1.0cm×1.0cm, 1.5cm×1.5cm, 2.0cm×2.0cm, etc., not exceeding 4cm. 2 The square size of .
[0025] In step (1) of the above method, the GaAs substrate is n-type doped with a doping concentration of 2×10 18 cm -3 .
[0026] In step (3) of the above method, the thickness of the evaporated ZnO film is 20-50 nm.
[0027] In step (3) of the above method, after the ZnO thin film is evaporated, it needs to be annealed under vacuum conditions at a temperature of 350°C-400°C.
[0028] In step (4) of the above method, the back electrode metal used can be one or a composite metal of Au, Pt, Ni, Ti and the like.
[0029] In step (4) of the above method, the thickness of the evaporated back electrode is 100-150 nm.
[0030] In step (4) of the above method, the annealing atmosphere of the evaporated back electrode is a nitrogen atmosphere, the annealing temperature is 300-350° C., and the annealing time is 30-60 seconds.
[0031] In step (6) of the above method, the PEDOT:PSS of the PEDOT:PSS@CNT film refers to an organic polymer, the full name of which is poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and the specific model is Clevios TM P 1000, CNT refers to carbon nanotubes. The composite layer is made by mixing PEDOT:PSS solution with CNT dispersion by ultrasonic means and then spin coating.
[0032] In step (6) of the above method, the concentration of the PEDOT:PSS@CNT solution is 10 mg / mL-30 mg / mL.
[0033] In step (6) of the above method, the preparation method of the PEDOT:PSS@CNT film is a spin coating method with a rotation speed of 3000-6000 rpm and a spin coating time of 10s-20s.
[0034] In step (6) of the above method, after the preparation of the PEDOT:PSS@CNT film is completed, it needs to be annealed under vacuum conditions at a temperature of 120°C-150°C.
[0035] In step (7) of the above method, the prepared top electrode is one or more composite metal electrodes selected from Ag, Cr, Ti, Ni and Au.
[0036] In step (7) of the above method, the thickness of the evaporated top electrode is 100-120 nm.
[0037] The principle of the present invention is as follows:
[0038] As a semiconductor, ZnO has a band relationship in the GaAs / PEDOT:PSS@CNT solar cell structure.Figure 3 As shown in the figure, a new band structure is introduced between the contact of the GaAs substrate and the Au back electrode by inserting the ZnO layer. It can be seen from the figure that compared with the simple GaAs / Au contact, the presence of the ZnO electron transport layer reduces the electron transition energy barrier from 1.03eV to 0.8eV, and the conduction band bottom position between the GaAs substrate and the ZnO electron transport layer differs by only 0.23eV, which can effectively reduce the potential barrier of electron transmission, thereby increasing the probability of electron transition. In addition, the addition of CNT improves the hole mobility of the PEDOT:PSS@CNT layer and promotes the separation of carriers, thereby achieving the purpose of improving device performance.
[0039] Compared with the existing technology, the present invention has the following advantages and beneficial effects:
[0040] Compared with the current common GaAs / PEDOT:PSS heterojunction solar cells, the preparation of the electron transport layer can be achieved through a simple evaporation and annealing process, which can improve device performance while maintaining a low cost. In addition, the insertion of the ZnO layer can promote the migration of electrons, and the application of the PEDOT:PSS@CNT layer can reduce carrier recombination, thereby improving device performance without conflicting with other functional layers. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the structure of a GaAs / PEDOT:PSS@CNT heterojunction solar cell in an embodiment of the present invention;
[0042] Figure 2 The molecular structure diagram of the PEDOT:PSS conductive polymer used in the present invention;
[0043] Figure 3 The energy band relationship diagram of the three when the ZnO electron transport layer used in the present invention is between the GaAs and Au back electrodes;
[0044] Figure 4 The JV curve of the GaAs / PEDOT:PSS@CNT heterojunction solar cell in the embodiment of the present invention;
[0045] Figure 1 The components are as follows:
[0046] Au back electrode 1, ZnO electron transport layer 2, GaAs substrate 3, PEDOT:PSS@CNT layer 4, top electrode 5. DETAILED DESCRIPTION
[0047] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0048] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0049] Example 1
[0050] A method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with a novel electron transport layer in this embodiment, the structural schematic diagram of which is shown in FIG. Figure 1 As shown, it includes an Au back electrode 1, a ZnO electron transport layer 2, a GaAs substrate 3, a PEDOT:PSS@CNT layer 4, and a top electrode 5 which are stacked in sequence from bottom to top.
[0051] The GaAs / PEDOT:PSS@CNT heterojunction solar cell is prepared in the following manner:
[0052] (1) Splitting the GaAs substrate into 1.0 cm × 1.0 cm squares as required;
[0053] (2) The segmented GaAs substrates were ultrasonically cleaned for 5 minutes using isopropanol, ethanol, and deionized water to remove organic matter on the surface, and then the intrinsic oxide layer on the surface of the GaAs substrate was removed using 10% by mass dilute hydrochloric acid;
[0054] (3) using electron beam evaporation to deposit a 30 nm thick ZnO layer on the back of the n-type doped GaAs substrate;
[0055] (4) annealing the GaAs substrate with the ZnO layer at 350° C. for 10 minutes under vacuum conditions;
[0056] (5) A 120 nm thick Au layer was evaporated on the ZnO layer as the back electrode;
[0057] (6) sending the substrate with the Au back electrode evaporated into an annealing furnace for rapid annealing in a nitrogen atmosphere at a temperature of 320°C and an annealing time of 30 seconds;
[0058] (7) Spin-coat a layer of PEDOT@CNT mixed solution on the upper surface of the GaAs substrate. The PEDOT:PSS concentration of the mixed solution precursor is 15 mg / mL, and the CNT dispersion liquid concentration is 1×
[0059] 10 -3 mg / ml, the volume fraction of the mixed solution PEDOT:PSS was 80%, and it was spin-coated at 3000 rpm for 15 seconds;
[0060] (8) annealing the spin-coated PEDOT:PSS@CNT film under vacuum conditions at a temperature of 130 °C for 5 min;
[0061] (9) A 110 nm Au layer was evaporated on the annealed PEDOT:PSS as the top electrode.
[0062] Figure 4 This is the JV curve of the GaAs / PEDOT:PSS@CNT heterojunction solar cell prepared in Example 1.
[0063] The open circuit voltage of the solar cell is 0.55V and the current density is 9.6mA / cm 2 , the filling factor is 66.7% and the photoelectric conversion efficiency is 3.52%.
[0064] Example 2
[0065] (1) Splitting the GaAs substrate into 1.0 cm × 1.0 cm squares as required;
[0066] (2) The segmented GaAs substrates were ultrasonically cleaned for 5 minutes using isopropanol, ethanol, and deionized water to remove organic matter on the surface, and then the intrinsic oxide layer on the surface of the GaAs substrate was removed using 10% by mass dilute hydrochloric acid;
[0067] (3) using electron beam evaporation to deposit a 30 nm ZnO layer on the back of the n-type doped GaAs substrate;
[0068] (4) annealing the GaAs substrate with the ZnO layer at 400° C. for 10 minutes under vacuum conditions;
[0069] (5) Evaporate a 120 nm Au layer on the ZnO layer as the back electrode;
[0070] (6) sending the substrate with the Au back electrode evaporated into an annealing furnace for rapid annealing in a nitrogen atmosphere at a temperature of 320°C and an annealing time of 30 seconds;
[0071] (7) Spin-coat a layer of PEDOT:PSS@CNT solution on the upper surface of the GaAs substrate. The PEDOT:PSS concentration of the mixed solution precursor is 15 mg / mL, and the CNT solution concentration is 1×10 -3 mg / ml, the volume fraction of the mixed solution PEDOT:PSS was 70%, and it was spin-coated at 3000 rpm for 15 seconds;
[0072] (8) annealing the spin-coated PEDOT:PSS@CNT film under vacuum conditions at a temperature of 130 °C for 5 min;
[0073] (9) A 110 nm Au layer was evaporated on the annealed PEDOT:PSS@CNT as the top electrode.
[0074] Example 3
[0075] (1) Splitting the GaAs substrate into 1.0 cm × 1.0 cm squares as required;
[0076] (2) The segmented GaAs substrates were ultrasonically cleaned for 5 minutes using isopropanol, ethanol, and deionized water to remove organic matter on the surface, and then the intrinsic oxide layer on the surface of the GaAs substrate was removed using 10% by mass dilute hydrochloric acid;
[0077] (3) using electron beam evaporation to deposit a 30 nm ZnO layer on the back of the n-type doped GaAs substrate;
[0078] (4) annealing the GaAs substrate with the ZnO layer at 400° C. for 10 minutes under vacuum conditions;
[0079] (5) Evaporate a 120 nm Au layer on the ZnO layer as the back electrode;
[0080] (6) sending the substrate with the Au back electrode evaporated into an annealing furnace for rapid annealing in a nitrogen atmosphere at a temperature of 330°C and an annealing time of 30 seconds;
[0081] (7) Spin-coat a layer of PDOTE:PSS@CNT composite solution on the upper surface of the GaAs substrate. The PEDOT:PSS concentration of the mixed solution precursor is 15 mg / mL, and the CNT solution concentration is 1×10 -3 mg / ml, the volume fraction of the mixed solution PEDOT:PSS was 70%, and it was spin-coated at 3000 rpm for 15 seconds;
[0083] (8) annealing the spin-coated PEDOT:PSS@CNT film under vacuum conditions at a temperature of 150°C for 5 minutes;
[0084] (9) A layer of Ag was evaporated on the annealed PEDOT:PSS as the top electrode.
[0085] Comparative Example 1
[0086] This comparative example is a method for preparing a GaAs / PEDOT:PSS heterojunction solar cell, and its structural schematic diagram is shown in FIG. Figure 1 As shown, it includes a back electrode, a GaAs substrate, a PEDOT:PSS layer, and a top electrode stacked in sequence from bottom to top.
[0087] The GaAs / PEDOT:PSS heterojunction solar cell is prepared in the following manner:
[0088] (1) Splitting the GaAs substrate into 1.0 cm × 1.0 cm squares as required;
[0089] (2) The segmented GaAs substrates were ultrasonically cleaned with isopropanol, ethanol and deionized water for 5 min.
[0090] minutes to wash away the organic matter on the surface, and then use 10% mass fraction of dilute hydrochloric acid to remove the intrinsic oxide layer on the surface of the GaAs substrate;
[0091] (3) Using electron beam evaporation method, a 120 nm Au layer is deposited on the back of the n-type doped GaAs substrate as the back electrode;
[0092] (4) Rapidly annealing the n-type GaAs substrate with Au back electrode in a nitrogen atmosphere at 350°C for 30 seconds;
[0093] (5) Spin coating a layer of PDOTE:PSS solution on the upper surface of the GaAs substrate, the solution concentration is 15 mg / mL, and the spin coating is performed at a rotation speed of 3000 rpm for 15 seconds;
[0094] (6) annealing the spin-coated PEDOT:PSS solution under vacuum conditions at a temperature of 110°C for 5 minutes;
[0095] (7) A 120 nm Ag layer was evaporated on the annealed PEDOT:PSS as the top electrode.
[0096] The device performance of the GaAs / PEDOT:PSS heterojunction solar cell prepared in Example 1 is shown in Table 1, wherein the open circuit voltage of the solar cell is 0.47 V and the current density is 3.1 mA / cm 2 , the filling factor is
[0097] 48.3%, and the photoelectric conversion efficiency is 0.70%.
[0098] Comparative Example 2
[0099] This comparative example is a method for preparing a GaAs / graphene heterojunction solar cell, and its structural schematic diagram is shown in FIG. Figure 1 As shown, it includes a back electrode, a GaAs substrate, a graphene layer, and a top electrode stacked in sequence from bottom to top.
[0100] The GaAs / graphene heterojunction solar cell is prepared in the following manner:
[0101] (1) Splitting the GaAs substrate into 0.5 cm × 0.5 cm squares as required;
[0102] (2) The segmented GaAs substrates were ultrasonically cleaned for 5 minutes using isopropanol, ethanol, and deionized water to remove organic matter on the surface, and then the intrinsic oxide layer on the surface of the GaAs substrate was removed using 10% by mass dilute hydrochloric acid;
[0103] (3) Using electron beam evaporation method, a 120 nm Au layer is deposited on the back of the n-type doped GaAs substrate as the back electrode;
[0104] (4) Rapidly annealing the n-type GaAs substrate with Au back electrode in a nitrogen atmosphere at 350°C for 30 seconds;
[0105] (5) Cut the purchased graphene film into 0.5 cm × 0.5 cm squares as needed, place it in an aqueous solution for wet transfer, and transfer the graphene to a GaAs substrate with an Au back electrode;
[0106] (6) placing the GaAs substrate with graphene transferred thereon in a vacuum reactor, using a machine to extract the water therein, then dripping a 50° C. acetone solution on the graphene surface to remove the PMMA involved therein, and washing away the acetone to obtain a pure GaAs / graphene heterojunction;
[0107] (7) A 120 nm Ag layer was evaporated on the annealed PEDOT:PSS as the top electrode.
[0108] The device performance of the GaAs / graphene heterojunction solar cell prepared in Example 2 is shown in Table 1, wherein the open circuit voltage of the solar cell is 0.51 V and the current density is 10.06 mA / cm 2 , the filling factor is
[0109] 51.98%, and the photoelectric conversion efficiency is 2.65%.
[0110] The preparation conditions of Comparative Examples 1 to 2 are similar to those of Example 1, except that no ZnO electron transport layer and CNT are used. In addition, since Comparative Example 2 uses two-dimensional materials to prepare heterojunctions, the price is higher than that of organic materials and is not suitable for large-scale production.
[0111] The parameters of comparative examples 1 to 2 were compared with those of embodiments 1 to 3 by testing with a solar simulator, and their performance parameters are shown in Table 1.
[0112] Table 1 Performance parameters of GaAs heterojunction solar cells obtained in Examples 1 to 3 and Comparative Examples 1 to 2
[0113]
[0114]
[0115] As can be seen from Table 1, compared with Comparative Examples 1 to 2, the filling factors of Examples 1 to 3 are significantly improved, which is related to the property of PEDOT:PSS@CNT that it is easy to form good contact, which can directly improve the device performance. In addition, compared with Comparative Example 1 without an electron transport layer, the current density of Examples 1 to 3 is significantly improved, which proves the role of the ZnO electron transport layer, which can promote electron transport and carrier separation, thereby improving the device current.
[0116] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer, characterized in that: The steps include: (1) Using electron beam evaporation method to evaporate a layer of ZnO on the back of GaAs substrate as an electron transport layer; (2) Evaporating a layer of Au on the surface of the ZnO film as the back electrode; (3) Preparation of PEDOT:PSS@CNT thin film on GaAs substrate surface; (4) Evaporating a layer of one or more composite electrodes selected from Ag, Cr, Ti, Ni, and Au on the surface of PEDOT:PSS@CNT.
2. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 1, characterized in that: The GaAs substrate is n-type doped.
3. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 1, characterized in that: In step (3), the preparation method of the PEDOT:PSS@CNT film is a spin coating method with a rotation speed of 3000-6000 rpm and a spin coating time of 10s-20s.
4. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 1, characterized in that: In step (1), after the ZnO thin film is evaporated, it needs to be annealed under vacuum conditions at a temperature of 350°C-400°C.
5. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 1, characterized in that: In step (3), after the preparation of the PEDOT:PSS@CNT film is completed, it needs to be annealed under vacuum conditions at a temperature of 120°C-150°C.
6. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 1, characterized in that: In step (3), PEDOT:PSS in the PEDOT:PSS@CNT film layer refers to an organic polymer, whose full Chinese name is poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, and CNT refers to carbon nanotubes; the composite layer is prepared by mixing the PEDOT:PSS solution and the CNT dispersion by ultrasonic means and then spin coating.
7. The method for preparing a GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 6, characterized in that: The concentration of PEDOT:PSS solution is 10mg / mL-30mg / mL, and the concentration of CNT dispersion is 1×10 -3 mg / ml~3×10 -3 mg / ml; the volume fraction of PEDOT:PSS solution in the PEDOT:PSS@CNT mixed solution is 30% to 90%.
8. A GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer prepared by the preparation method according to any one of claims 1 to 7.
9. A GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 8, characterized in that: The structure of the solar cell from bottom to top is Au back electrode, ZnO electron transport layer, GaAs substrate, PEDOT:PSS@CNT layer and top electrode.
10. A GaAs / PEDOT:PSS@CNT heterojunction solar cell with an electron transport layer according to claim 8, characterized in that: The open circuit voltage of the solar cell is 0.50-0.55V, and the current density is 8.1-10.8mA / cm 2 , the filling factor is 62.1~66.7%, and the photoelectric conversion efficiency is 2.77~3.53%.
Citation Information
Patent Citations
Composite flexible transparent conductive film and preparation method thereof
CN109887647A
Solar cell with PEDOT: PSS / graphene / GaAs structure and preparation method thereof
CN115000215A
Gallium arsenide solar cell and preparation method and application thereof
CN118301949A
Carbon nanotube / silver nanowire composite film and gallium arsenide-based heterojunction solar cell thereof and preparation method
WO2023184966A1